(untitled) (Journal of Technology and Vocational Studies, 2026)
The implementation of Unmanned Aerial Vehicles (UAVs) in the agricultural sector has undergone a paradigm shift from passive monitoring to active functional intervention. However, limited battery autonomy and flight instability induced by dynamic payload variations remain critical bottlenecks for large-scale industrial adoption. This paper presents a systematic review of the evolution of agricultural UAVs, focusing on the emergence of tethered hexacopter systems (TKT-6) as a robust solution for persistent, long-duration missions in complex topographies. We synthesize high-impact research (2021–2025) covering high-voltage power transmission, umbilical cable dynamics, and advanced control architectures. A primary emphasis is placed on the transition from conventional PID frameworks to adaptive-robust control strategies. Comparative analysis reveals that the synergy between Disturbance Observers (DOB) and Sliding Mode Control (SMC) significantly mitigates attitude errors and suppresses the "anchor effect" caused by tether tension. Our findings demonstrate that the TKT-6 system effectively maintains positioning precision below 0.2 m even under time-varying payload conditions, offering a transformative approach for precision spraying in steep-terrain orchards, such as mangosteen cultivation.